A SA study into the adherence to the International Labour Organisation's Code of Practice on HIV/AIDS and the world of work in HIV/AIDS workplace policy content development - Klopper, Karensa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm) -- University of Stellenbosch, 2004.